Health- and skill-related physical fitness profile of Brazilian children and adolescents: a systematic review - Pedretti, Augusto (2020)
Since 1994, the Projeto Esporte Brasil (PROESP-Br) battery tests has been used to evaluate health- and skill-related physical fitness among aged 6-17 Brazilian schoolchildren. The aim of this study was to delineate the Brazilian children and youth’s physical fitness profile from a systematic review over studies that used the PROESP-Br proposal. The search was carried at PubMed, ScienceDirect, Lilacs, SciELO and Google Scholar. Original studies published between 1994 and 2017 about physical fitness (health and/or motor performance) with schoolchildren (children and/or adolescents) that used the PROESP-Br battery test were included. A total of 13.582 participants  were evaluated to health-related fitness and 276 to skill-related fitness from 18 included studies. The methodological quality was evaluated using the Newcastle-Ottawa quality assessment scale adapted version. The results show that 27-30% of youngsters are at health “risk zone” for Body Mass Index (BMI), 70% for cardiorespiratory fitness (CRF), 50% and 65% for flexibility (FLEX) and muscular strength (MST), respectively. The data concerning skill-related fitness were inconsistent. In summary, the results suggest that Brazilian children and adolescents have low cardiovascular health level (BMI/CRF), mainly regarding CRF, and low muscle health level (FLEX/MST). We emphasize that the lack of studies regarding skill-related fitness, make it impossible to describe the profile of the components of this construct.